DIVERSITY AND SPATIO-TEMPORAL DISTRIBUTION OF FISH SPECIES IN TIGA DAM, KANO STATE - ABDULKARIM, M; MAGAJI, I. M; YUSUF, Z. A; MAGAJI, N.S (Nigerian Journal of Fisheries, 2020)
The study determined the composition, diversity, and Spatio-temporal distribution of fish species in Tiga dam, Kano State, Nigeria. Sampling sites were visited at an interval of two weeks during the study period (May 2018 – March 2019). Fish samples were randomly collected from Fishers fishing in headwater, middle water, and tailwater. Relative abundance and biodiversity indices were calculated. Spatio-temporal distribution of fish was evaluated using Kolmogorov-Smirnov statistics of the goodness of fit. Nine fish species representing seven families comprising 4002 individual fish were identified. The family Alestidae and Claridae had two species each while Bagridae, Cichlidae, Mochokidae, Mormyridae, and Osteoglossidae had one species each. Oreochromis niloticus (49.18%) was the most abundant fish species caught in the dam while the least abundant was Heterobranchus bidorsalis (0.30%). Alestes dentex, Bagrus docmak, Clarias gariepinus, Heterobranchus bidorsalis and Heterotis niloticus were evenly distributed while Brycinus nurse, O. niloticus, Synodontis schall, and Mormyrus rume were not evenly distributed. The dam was diverse with 0.64 and 0.32 as Evenness and Simpson’s dominance indices respectively. Fishers can fish with relatively lesser efforts and catch more fish at the middle water; however, there is a need to carry out a stock assessment of the fish species in the dam.